2017
DOI: 10.1016/j.ajo.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cytokine Levels in Tears and Clinical Correlations After Intense Pulsed Light Treating Meibomian Gland Dysfunction

Abstract: The study results suggest that IPL can significantly reduce inflammatory markers in tears of patients suffering with DED owing to MGD after IPL treatment. These findings indicate that IL-17A and IL-6 play roles in the pathogenesis of DED owing to MGD, and the reduction of the inflammatory factors is consistent with the improvement of partial clinical symptoms and signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
175
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 47 publications
9
175
2
4
Order By: Relevance
“…Improvements in dry eye symptomology scores, tear film stability, lipid layer thickness, meibomian gland expressibility and capping, and corneal fluorescein staining have been reported following three to four sessions of IPL therapy in these randomized studies [14,15,28,31,38]. Furthermore, reductions in the expression of IL-6, IL-17A, and PGE2 was observed to be associated with improvements in clinical ocular surface parameters in a recent double-masked, paired eye, randomized, sham-controlled trial [15]. Another double-masked, parallelgroup, randomized, sham-controlled trial reported inhibition of periocular Corneybacterium macginleyi load following four sessions of IPL therapy [14].…”
Section: Clinical Efficacymentioning
confidence: 95%
See 2 more Smart Citations
“…Improvements in dry eye symptomology scores, tear film stability, lipid layer thickness, meibomian gland expressibility and capping, and corneal fluorescein staining have been reported following three to four sessions of IPL therapy in these randomized studies [14,15,28,31,38]. Furthermore, reductions in the expression of IL-6, IL-17A, and PGE2 was observed to be associated with improvements in clinical ocular surface parameters in a recent double-masked, paired eye, randomized, sham-controlled trial [15]. Another double-masked, parallelgroup, randomized, sham-controlled trial reported inhibition of periocular Corneybacterium macginleyi load following four sessions of IPL therapy [14].…”
Section: Clinical Efficacymentioning
confidence: 95%
“…In addition, a recent randomized trial showed that a three-month course of IPL therapy inhibited periocular Corneybacterium macginleyi load [14]. Furthermore, the anti-inflammatory action of IPL therapy has also been demonstrated with the reduction of inflammatory markers in tear samples, including IL-4, IL-6, IL-10, IL-17A, TNF-α, and PGE2 [15,16].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry eye cytokine analysis caused by MGD showed an increase in CX3CL1, IL-1Ra, IL-6, IL-8 / CXCL8, and EGF [12][13][14]. These markers should be further investigated for understanding the antiin lammatory mechanism and posttreatment measurement and a possible relationship with IPL failure [18][19][20].…”
Section: Treatment Eff Ectivenessmentioning
confidence: 99%
“…15 Decreasing the threshold of the pain when the ionic concentration is stabilized on both sides of the cellular membrane during sensitive terminations affects the sensory nerve fibers thereby delaying neuronal depolarization.…”
mentioning
confidence: 99%